V. V. von Wal as Head of Vilnius Province in 1901—1902 - M. N. Krot (Научный диалог)
The activities of one of the typical representatives of the Russian regional bureaucracy of the second half of the 19th — early 20th centuries — Viktor Vilhelmovich von Wal as governor of Vilnius province, which he held from 1901 to 1902 is examined in the article.  Particular attention is paid to the circumstances of his appointment to this position, which was due to attempts at administrative reorganization of the management of the northwestern outskirts of Russia. A brief analysis of the socio-political situation that had developed by the beginning of the 20th century in the Vilnius province is given and it is indicated that the most acute problem during this period was the active labor movement, which had a mixed socio-ethnic character in the region. It is concluded that the management model implemented by von Wahl, which was based on the traditional administrative-power dominant, did not correspond to the situation in the region and provoked an increase in the degree of violence in the province. It is noted that, despite the short-term tenure of von Waal as governor of Vilna, it had a number of important consequences, demonstrating the premature liquidation of the institution of the governor-general in the region and the need to soften the administrative policy towards the local population.